Proximate and phytochemical analysis of Acanthus ilicifolius hot water extract from three different growing locations - RIDWANTI BATUBARA; T. ISMANELLY HANUM; ODING AFFANDI; MIMI NURMINAH; INA WINARNI; SALEHA HANNUM; ORYZA YULIA YASMIN; SHAFIRA CHAIRUNNISA CHERY; AFIFUDDIN DALIMUNTE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Batubara R, Hanum TI, Affandi O, Nurminah M, Winarni I, Hannum S, Yasmin OY, Chery SC, Dalimunte A. 2025. Proximate and phytochemical analysis of Acanthus ilicifolius hot water extract from three different growing locations. Biodiversitas 26: 1641-1651. Jeruju (Acanthus ilicifolius) is a tide-dependent plant and often obtains more freshwater supply. The chemical composition of this plant needs to be explored so that consumers can obtain the required information, particularly regarding the use of A. ilicifolius hot water extract. Therefore, this research aimed to determine proximate and phytochemical content of A. ilicifolius from three different growing locations. Proximate analysis was carried out by testing water, ash, fat, and protein composition, while phytochemical tests and GC-MS (Gas Chromatography Mass Spectrometry) were used to determine the number and names of chemical compounds, respectively. The results showed that ash, fat, and protein composition of A. ilicifolius from the three sample locations were not statistically different. Based on SNI 3945-2016 and SNI 01-4453-1998, water content met the standard of 2.11-7.47%, while ash content did not fulfill the requirement of 0.56-0.59%. Fat and protein content ranging from 8.58 to 10.22% and 19 to 19.95% had no standard specification. Phytochemical test results of hot water extract showed that the compounds from the three sample locations were the same, including flavonoids, glycosides, steroids, triterpenoids, saponins, and tannins. Based on GC-MS, the main compound in hot water extract of A. ilicifolius sampled from Pasar Rawa Village was 2(3H)-Benzoxazolone. In comparison, the main compounds from Percut Village and Paya Pasir Village were found to be dodecanoic acid, 1,2,3-propanediol ester, and dodecyl palmitate.